The hunger of the gods - Gwynne, John, 1968- (New York : Orbit, 2022)
Lik-Rifa, the dragon god of legend, has been freed from her eternal prison. Now she plots a new age of blood and conquest. As Orka continues the hunt for her missing son, the Bloodsworn sweep south in a desperate race to save one of their own--and Varg takes the first steps on the path of vengeance. Elvar has sworn to fulfil her blood oath and rescue a prisoner from the clutches of Lik-Rifa and her dragonborn followers, but first she must persuade the Battle-Grim to follow her. Yet even the might of the Bloodsworn and Battle-Grim cannot stand alone against a dragon god. Their hope lies within the mad writings of a chained god. A book of forbidden magic with the power to raise the wolf god Ulfrir from the dead...and bring about a battle that will shake the foundations of the earth.
Keywords: Gods -- Fiction; Dragons -- Fiction; Imaginary wars and battles -- Fiction; Soldiers -- Fiction; Monsters -- Fiction; Hunters -- Fiction; Nobility -- Fiction; Magic -- Fiction; Fantasy fiction